Het Onding Kunst. - Galerie Stalker, Breda (Breda : Galerie Stalker, 1988)
Liptow, Hilmar ; De Paepe, Simone ; Stikker, Carolien ; Lizene, Jacques ; Bure-soh ; Allais, Alphonse ; Schraenen, Guy ; De Vylder, Paul ; Fitzsimons, Connie ; Meisner, Bruce ; Francois, Charles ; Schepers, Marc ; De Clerq, Lode ; Antoine, Pierre ; Bay, Didier ; Elie, Francois ; Van Maele, Marcel ; Devos, Danny
Het Onding Kunst, Galerie Stalker, Breda, maart 1988
boek